Spatial Analysis Using Exploratory Spatial Data Analysis (ESDA) of Child Marriage Among Women 15-24 Years old in Indonesia - Regina Tambunan; Kemal N. Siregar; Tiopan Sipahutar (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Child marriage, which has existed for centuries, is a complex issue, deeply rooted in gender inequality, tradition, and poverty. Child marriage is increasingly recognized as a violation of girls' rights because it effectively ends education, deprives any opportunity to acquire vocational and life skills, exposes children to the risk of early pregnancy, bearing children, and motherhood before being physically and psychologically ready, increasing the risk of sexual violence and HIV infection Objective: This study aims to conduct spatial analysis to determine the spatial autocorrelation between provinces in Indonesia based on the number of child marriages influenced by reproductive system knowledge in women aged 15-24 years who marry children (<=18 years) in Indonesia. Method: This study used a cross-sectional approach covering all provinces of Indonesia using raw data from the 2017 Indonesian Demographic and Health Survey organized by BPS in collaboration with BKKBN and the Ministry of Health. Data on the distribution of child marriage events will be analyzed using Exploratory Spatial Data Analysis (ESDA) with GeoDa application version 16. Result: Indonesia with 34 provinces has a minimum value of zero (0) child marriage maximum of 9, a median of 1, an average of 1.67, and a standard deviation of 2.11374. In addition, there is a positive autocorrelation between the number of child marriages and knowledge of the reproductive system. For bivariate spatial analysis that associates the number of child marriages in Indonesia with knowledge of the reproductive system, a coefficient correlation of 0.679 is known so that it can be interpreted that the number of child marriages has a moderate positive correlation. Conclusion: It was concluded that the results of global autocorrelation for child marriage cases using Moran's I with a queen contiguity weighting matrix are known to have positive spatial autocorrelation or form a grouping pattern so that it can be interpreted spatially the number of child marriages in one province with other provinces is interconnected, especially neighboring ones.